Effects of different sub types and timing of childhood maltreatment on sperm small non-coding RNA levels - Iliadou, Sofia (My University, 2025)
Background: Childhood maltreatment (CME) consisting of various forms of abuse, including physical and emotional abuse and neglect, and has been extensively linked to harmful effects on psychological and physiological well-being. For instance, maltreatment has been shown to be associated with increased levels of cortisol, a hormone critical to stress response, and alterations in growth hormone levels, which can have cascading effects on overall health (Jensen et al., 1991). Furthermore, emerging studies highlight the impact of CME on reproductive health, including altered sperm epigenetics, such as small non-coding RNA (sncRNA) profiles and DNA methylation patterns, which may influence fertility and offspring health (Gapp et al., 2014; Rodgers et al., 2013). This thesis focuses on two key sncRNAs identified in animal studies to have intergenerational effects, the miR-34c and miR-449a. This intersection of psychological trauma and physiological outcomes highlights the need for a comprehensive understanding of the mechanisms by which childhood maltreatment affects individuals across their lifespan. Methods: This study investigates the associations between childhood maltreatment experiences (CME), measured via the Trauma and Distress Scale (TADS), and sperm small non-coding RNAs (sncRNAs) miR-34c and miR-449a. It builds upon data from the FinnBrain Birth Cohort Study and subsequent follow-ups. Data were derived from 30 male participants aged 30–48 years (mean: 39,1 ± 5,0). CME exposure, including five factors: emotional neglect, emotional abuse, physical neglect, physical abuse, and sexual abuse, was assessed across three age periods: 0–6, 7–12, and 13–18 years. TADS scores were used to calculate cumulative and factor-specific CME exposure for each age range separately (5 factors x 3 age ranges) and due to high number of variables were entered into stepwise regression models that aimed to predict relative abundance of miR-34c. Key health variables were included as covariates in statistical testing; including BMI, depressive and anxiety symptoms, smoking, alcohol consumption, and sperm quality metrics. Statistical analyses were performed with stepwise linear regression models with a significance threshold of p < 0.05. Results: When examining the age window of maltreatment on the sperm miRNA-levels, it was found, that CME during puberty (7–12 years) was associated negatively with miR-34c levels (ß = -0,498, p = 0,010). In wider analysis studying the combination of type and age of maltreatment, physical neglect during early childhood (0–6 years) was negatively associated with decreased miR-34c levels (ß = -0,602, p = 0,001). When examining each type of maltreatment throughout childhood (0–18 years), emotional abuse has the strongest association with reduced miR-34c levels (ß = -0,500, p = 0,009). Unlike miR-34c, no statistically significant associations were found between CME and miR-449a levels, except for a potential link with sperm concentration (ß = -0,408, p = 0.039). Conclusion: There is growing evidence that CME has implications for reproductive and overall health outcomes in later life. Our findings emphasize the CME sensitive periods in childhood for epigenetic alterations in sperm sncRNAs, particularly miR-34c, to be puberty for overall maltreatment and early childhood in a combination with physical neglect. No significant associations were identified between CME exposure and miR-449a levels, suggesting that miR-449a may be less sensitive to early-life stress or influenced by other factors. Despite the identified associations, further research is necessary to clarify the underlying mechanisms and the extent to which these findings can be generalized beyond the studied population, and to develop interventions targeting the psychological and physiological effects of childhood maltreatment to mitigate long-term health risks.
Keywords: childhood maltreatment, epigenome, sperm cell, sncRNA